Study of phenol-formaldehyde oligomers derivatives structure by IR- and NMR-spectroscopy - Zubyk, H.; Plonska-Brzezinska, M.; Shyshchak, O.; Astakhova, O.; Bratychak, М. (Publishing House of Lviv Polytechnic National University, 2015)
Using IR-and NMR-spectroscopy (1H and 13C) the structure of functional oligomers based on novolac phenol-formaldehyde and polyglycidyl phenolformaldehyde oligomers has been characterized. The structure of modified phenol-formaldehyde oligomers has been confirmed by the presence of absorption bands and proton shifts corresponding to furan ring, methacrylic fragment, peroxy, hydroxyl, and phenol groups. За допомогою ІЧ- та ЯМР (1Н та 13С) спектроскопічних досліджень охарактеризовано будову функціональних олігомерів, отриманих на основі новолачного феноло-формальдегідного та полігліцидилфеноло-формальдегідного олігомерів. Структура модифікованих фенолоформальдегідних олігомерів доведена присутністю смуг поглинання та протонних зсувів, що віповідають фурановому кільцю, метакриловому фрагменту, пероксидним, гідроксильним та фенольним групам.
Дослідження будови похіднихфеноло-формальдегідних олігомерів методами ІЧ- та ЯМР-спектроскопії
Keywords: IR- and NMR-spectroscopy; phenol-formaldehyde oligomer; polyglycidyl phenol-formaldehyde oligomer; modification; methacrylate group; peroxide; ІЧ- та ЯМР спектроскопія; феноло- формальдегідний олігомер; полігліцидилфеноло-формальдегідний олігомер; модифікація; метакрилатна група; пероксид